The Effect of Employee Engagement, Marketing Capability and Innovation on Sustainable Customer Loyalty among MSMEs Customers in Indonesia - Dana Budiman; Andri Ardhiyansyah (Universitas Tidar, 2023)
The competitive landscape of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia underscores the importance of sustained customer loyalty as a strategic imperative for growth and resilience. This research explores the dynamic relationship between employee engagement, marketing capability, innovation, and their combined impact on sustainable customer loyalty in the Indonesian MSME sector. A sample of 275 respondents provided insights into their demographic profile and perceptions. The study used SPSS version 26 software in analyzing the data, including instrument tests, classical assumption tests, and hypothesis testing regarding the positive influence of employee engagement, marketing capability, and innovation on sustainable customer loyalty. The findings strongly support these relationships, highlighting the importance of employee engagement, marketing capability, and innovation as drivers of sustained customer loyalty. The implications of these findings extend to MSMEs practitioners, policymakers, and academics, emphasizing the need for strategic investments in these critical areas to enhance the long-term growth and sustainability of the MSME sector in Indonesia.